The Role of the Joint Procurement Agreement during the COVID-19 Pandemic: Assessing Its Usefulness and Discussing Its Potential to Support a European Health Union. (26th December 2020) - MCEVOY, Emma; FERRI, Delia
Abstract : In 2014, the European Joint Procurement Agreement (JPA) was introduced as an innovative instrument to organise the procurement of vaccines and medications in preparation for pandemics. An overriding purpose of the JPA is to secure equitable and cost-effective access to medical supplies for participating EU Member States during serious health crises. This article aims to understand the current use of the JPA in response to the COVID-19 pandemic. Post-analysis of the recent use of the JPA, the article will discuss how the regional procurement mechanism can be strengthened to support the development of a European Health Union. In particular, the article will firstly question whether the four recent JPA procurement actions facilitated equitable access to medical supplies and services. Secondly, it will ask whether the centralised procurement actions preserved the integrity of the Internal Market. The importance and originality of this study are that it addresses an instrument, the JPA, which has been largely overlooked by legal scholars, and it explores how the provisions for the joint procurement of medical countermeasures as included in Article 5 of Decision 1082/2013/EU on serious cross-border threats to health could be extended to support the functioning of a European Health Union.